Eight Dusts: Healing Rituals and Metaphysics of Dust among Nepalese Followers of a Japanese New Religion - Frisone, Marilena (E|C, 2023)
Every morning a group of Nepalese followers of the Japanese new religion called Tenrikyō (“Teachings of the Heavenly Wisdom”) gathers in a small room in Kathmandu and performs rituals and prayers, hoping to be able to experience the Joyous Life in this world. One of the topics often discussed after the prayer is the doctrine of the “eight dusts” (Jp. yattsu no hokori). According to it human nature is not inherently evil, and the selfish or unethical behaviour that sometimes characterises human actions, can simply be understood as the result of a bit of “dust” – eight types in fact – which has settled on an otherwise originally pure “heart/mind” (Jp. kokoro, Np. man). “Dust” is here conceptualised as “mistaken thoughts – that is, states of mind that do not accord with the intention of God”. From a semiotic point of view, dust thus plays here the actantial role of Anti-Subject, which needs to be removed through ethical practice and the ritual gestures of a sacred dance – in order to fully realise an Ethical Subject in conjunction with an Object of Value, the pure “heart/mind”. Dust is to the broom of God, what selfishness is to divine will. In this complex semi-symbolic use, dust, connected with dirt, is not only conceptualised in opposition to cleanness and purity, but also as the result of a selfish behaviour which has neglected the will of God. This paper, based on fifteen months of anthropological fieldwork in Nepal, will explore the moral and metaphysical implications of the doctrine of eight dusts as discussed among Nepalese followers of Tenrikyō, trying to show how dust may connect more in general to the ethical dimension of practice.